A smartphone app to improve the safety of patients undergoing treatment with oral antineoplastic agents: 4 years of experience in a university hospital - Villanueva-Bueno, Cristina; Collado-Borrell, Roberto; Escudero-Vilaplana, Vicente; Revuelta-Herrero, José Luis; Marzal-Alfaro, María Belén; González-Haba, Eva; Arranz-Arija, José Ángel; Osorio, Santiago; Herranz-Alonso, Ana; Sanjurjo-Saez, María (Frontiers in Public Health, 2022)
Objective This study aims to analyze the impact of the eOncosalud app on the management and follow-up of adverse events in patients receiving oral antineoplastic agents. Material and methods We performed an observational, prospective study of cancer outpatients treated with oral antineoplastic agents (OAA), monitored by the eOncoSalud app between August 2017 and October 2021. Safety variables were collected from eOncosalud: the number of adverse effects (AE); severity of the AE according to CTCAE, version 4.03; timelapse from app installation to first recorded AE; automatic recommendations issued; and the patient’s acceptance of the recommendations made. To assess the impact of the recommendations generated by the algorithm, we calculated the positive predictive value (PPV) as the number of recommendations accepted out of the total number of recommendations generated. Safety-related patient messages were also analyzed (AE, drug-drug interactions, drug administration). Result The app was downloaded and used by 186 patients (58.0% women), with a mean age of 59.0 years. A total of 1,368 adverse reactions were recorded, the most frequent being fatigue (19.37%), diarrhea (18.20%), and skin changes (9.21%). Regarding the recommendations issued by the app algorithm, 102 patients received 344 information brochures, 39 patients received 51 recommendations for supportive care to control AE, 60 patients received 240 recommendations to visit their primary care doctor, 14 patients received 16 recommendations to contact their specialist pharmacist or oncologist-hematologist, and 34 patients received 73 recommendations to go to the emergency room. The suggestion to go to the emergency room and contact the specialist pharmacist or oncologist-hematologist had a PPV of 0.51 and 0.35, respectively. Half of the patients (50.4%) used the messaging module. A total of 1,668 messages were sent. Of these, 47.8% were related to treatment safety: AE, 22.7%; drug-drug interactions, 20.6%; drug administration, 3.6%; and missing a dose, 1.0%. Conclusions The eOncosalud app enables close, real-time monitoring of patients treated with OAA. The automatic recommendations through the app's algorithm have optimized available healthcare resources. The app facilitated early detection of AE, thus enabling patients themselves to improve the safety of their treatment.